2016
DOI: 10.1111/ijfs.13333
|View full text |Cite
|
Sign up to set email alerts
|

Changing in processing yield and physical properties of frozen white shrimp (Penaeus vannamei) treated with lysine and sodium bicarbonate

Abstract: Summary The objective of this research was to investigate the phosphate alternative use of natural compound, lysine with sodium bicarbonate (NaHCO3), at low concentration for freezing of white shrimp (Penaeus vannamei). Shrimp were treated with lysine, NaHCO3 and lysine with NaHCO3 at various concentrations and frozen in an air‐blast freezer. Thawing yield, cooking yield, colour, texture and nanostructure of the sample were studied compared to the control (nontreated sample) and sodium tri‐polyphosphate (STPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Lysine has been used in pork sausage for improving texture and color, and for enhancing its yield (Zhou, Li, & Tan, ), as well as the yield of frozen shrimp after a freeze–thaw cycle (Wachirasiri et al., ). The use of lysine in combination with NaHCO 3 exhibited higher efficiency for retaining water, better than that in the control and by the use of lysine alone, as described in our previous study (Wachirasiri et al., ). Several studies reported that NaHCO 3 can improve the yield, texture, and color of frozen shrimp (Chantarasataporn et al., ; Lopkulkeirt et al., ).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Lysine has been used in pork sausage for improving texture and color, and for enhancing its yield (Zhou, Li, & Tan, ), as well as the yield of frozen shrimp after a freeze–thaw cycle (Wachirasiri et al., ). The use of lysine in combination with NaHCO 3 exhibited higher efficiency for retaining water, better than that in the control and by the use of lysine alone, as described in our previous study (Wachirasiri et al., ). Several studies reported that NaHCO 3 can improve the yield, texture, and color of frozen shrimp (Chantarasataporn et al., ; Lopkulkeirt et al., ).…”
Section: Resultssupporting
confidence: 78%
“…Increasing TBARS value indicated the formation of secondary lipid oxidation in products, resulting in rancidity and loss of product quality. Our previous study (Wachirasiri et al., ) found that the use of lysine, lysine/NaHCO 3 , and sodium tri‐polyphosphate (STPP) could reduce the TBARS of the freeze–thawed shrimp compared to that of the control, but not significantly different from that of the STPP‐treated sample ( P > 0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Banana skin is the food production waste, the mass fraction of the skin on the fruit is 30–40% . The utilization of banana skin is an actual problem for the countries with tropical and subtropical climates .…”
Section: Introductionmentioning
confidence: 99%
“…Banana skin is the food production waste, the mass fraction of the skin on the fruit is 30–40% . The utilization of banana skin is an actual problem for the countries with tropical and subtropical climates . Banana skin contains less cellulose, lignin and hemicellulose than fillers listed above, but it contains a significant amount of pectins (13–21%), starch (13%), fats (13%) and proteins (9%) (Table ) that contributes to its biodegradability .…”
Section: Introductionmentioning
confidence: 99%